Spatial resolution enhancement using deep learning and data augmentation for cloud-based infrastructure - Mohamed, Moataz Ahmed Abdelghaffar (2019)
Satellite data have fundamentally changed how we perceive and understand the world we live in. The amount of data produced is rapidly increasing and classical computing resources and processing tools are no longer sufﬁcient. These massive amounts of data require huge storage in addition to advanced computing capacity in order to allow users to beneﬁt from the derived datasets. Cloud computing has provided the required storage and computing capacity on a scalable level to add or remove resources according to requirements. Simultaneously, recent advances in data processing techniques such as Deep Learning (DL) have paved the way to integrated solutions for Earth Observation (EO) big data understanding.